AMYLOGRAPHY PROFILE AND MICROSTRUCTURE OF BENENG TARO BANTEN (Xanthosoma undipes K. Koch) STARCH - Vega Yoesepa Pamela; Winda Nurtiana; Bayu Meindrawan (University of Sultan Ageng Tirtayasa, 2019)
High demand of flour import for food applications was a big threaten for food security in Indonesia. The utilization of carbohydrate sources from local food plants can be an alternative to overcome this problem. Beneng taro is a local food from Pandeglang, Banten Province that potential to be used as composite flour. The application of food products, Beneng taro can be used as starch. The purpose of this study is to analyze the characteristics of Beneng taro starch on the amylographic profile of the granules and their morphology. The extraction method used is wet extraction using distilled water. The ratio of taro and distilled water used is 1: 3. The optimum formulation (1: 3) was then tested for morphological properties using SEM instrument and amylograph profile using RVA instrument. SEM test results showed uniform starch granules and polygon-shaped granules. The amylographic profile shown a maximum viscosity of 1075cP with a temperature of 92.4oC at 270 seconds, a set back value of 186 cP and a break down of 214 cP. Based on the amylographic profile, beneng taro starch still has many weaknesses (large set back and break down) so it needs to be modified so that it can be applied to food products.